2015
DOI: 10.1155/2015/979515
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota: Association with NAFLD and Metabolic Disturbances

Abstract: Nonalcoholic fatty liver disease is the hepatic expression of metabolic syndrome, being frequently associated with obesity, insulin resistance, and dyslipidemia. Recent lines of evidence have demonstrated a role of gut microbiota in insulin resistance, obesity, and associated metabolic disturbances, raising the interest in its relationship with NAFLD pathogenesis. Therefore, intestinal microbiota has emerged as a potential factor involved in NAFLD, through different pathways, including its influence in energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 52 publications
3
75
0
7
Order By: Relevance
“…Intestinal microbiota composition modulates glucose homeostasis and hepatic lipid metabolism, contributing to NAFLD development as an environmental factor [29,66].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%
“…Intestinal microbiota composition modulates glucose homeostasis and hepatic lipid metabolism, contributing to NAFLD development as an environmental factor [29,66].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%
“…Specifically, the gut microbiota can influence host metabolism through gut signaling pathways that affect insulin resistance, lipid metabolism, ethanol production, and inflammation (26, 29). The mechanisms by which the microbiota induce obesity include increasing gut permeability that causes bacterial translocation and increased hepatic and systemic inflammation, production of short-chain fatty acids (SCFAs), and greater extraction of energy from the diet (26,35).Little is known about the effect of aerobic fitness on the microbiome and its potential role in disease development. Therefore, we used the HCR/LCR rat model system to determine 1) whether intrinsic aerobic fitness affects the cecal microbiota; and 2) whether acute changes in the microbiota following 3 days of HFD feeding are associated with development of hepatic steatosis.…”
mentioning
confidence: 99%
“…Barbara D et al reported that FOS supplement reduced hepatic triglyceride accumulation in n-3 PUFA-depleted diet-induced NAFLD model by altering microbiota composition and increasing production of GLP-1 [121]. Meanwhile, FOS supplementation stimulated fatty acid oxidation by activating peroxisome proliferatoractivated receptor-alpha (PPAR-α) and reduced cholesterol accumulation by inhibiting SREBP-2 in liver without affecting SREBP-1 expression and activity [121,122]. Lactulose is a prebiotic that promotes the growth of lactic acid bacteria and Bifidobacteria [123].…”
Section: Gut Microbiota-targeted Therapy With Prebioticmentioning
confidence: 99%